Kedudukan Hukum Aparatur Sipil Negara dalam Sengketa Kepegawaian: Tanggung Jawab, Perlindungan, dan Mekanisme Penyelesaian - Rosada, Dede; Sulastri, Dewi (SPT. haria Journal and Education Center Publishing, 2026)
State Civil Apparatus (ASN) holds a central role in the bureaucracy, yet they often face employment disputes that test their legal standing. This study examines the legal position of ASN in employment disputes in Indonesia, covering aspects of responsibility, protection, and resolution mechanisms. Using a normative-empirical approach, the research analyzes the regulatory framework, such as Law No. 5 of 2014, judicial practices in the Administrative Court (PTUN), and challenges like political intervention and procedural inconsistencies. The findings indicate that the legal protection of ASN highly depends on procedural certainty (due process) and the independence of the examination process. This study recommends strengthening mediation mechanisms, clarifying administrative procedures, and enhancing the external oversight role of the Ombudsman to ensure justice for ASN.